A water-based composite ink

By combining high proportion of aqueous polyurethane and low proportion of modified aqueous acrylic resin in aqueous inks, and combining the coating technology of modified starch and propylene glycol methyl ether acetate, the ratio of the dispersion medium is optimized to form a unique network structure, which solves the problem of poor adhesion of existing aqueous inks and achieves high adhesion and stability effects.

CN119144189BActive Publication Date: 2025-04-01SHAANXI XINAOHUA MATERIAL TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411661944.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-01
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The adhesion of existing water-based inks is poor and it is difficult to meet the requirements of high adhesion and stability.

Method used

High proportion of aqueous polyurethane and low proportion of modified aqueous acrylic resin are used for compounding, combined with the coating technology of modified starch and propylene glycol methyl ether acetate, the ratio of the dispersion medium is optimized to form a unique network structure to improve the adhesion of the ink.

Benefits of technology

It significantly improves the adhesion and color uniformity of the aqueous composite ink, enhances the chemical bonding or physical adsorption between the ink and the substrate, and improves the overall cohesion and stability of the ink.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application discloses a water-based composite ink, which relates to the technical field of inks. The water-based composite ink comprises 50-70 parts by mass of water-based resin, 15-25 parts by mass of pigment, 12-18 parts by mass of modified starch, 0.1-0.5 parts by mass of defoamer, 30-60 parts by mass of dispersion medium and 3-5 parts by mass of triethanolamine; the water-based resin comprises modified water-based acrylic resin and water-based polyurethane; the dispersion medium comprises water, anhydrous ethanol and propylene glycol ethers. The water-based composite ink prepared by the present application not only has good adhesion, but also has stable and uniform coloring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inks, and in particular to a water-based composite ink. Background Art

[0002] Water-based ink is a printing ink system with water as the main solvent or dispersion medium. Its key component is the binder, which is usually made of water-soluble resin, supplemented with organic dyes, functional solvents and various necessary additives, and ground and processed. Compared with traditional solvent-based inks, the biggest advantage of water-based composite inks is its environmental friendliness, which greatly reduces the emission of volatile organic compounds (VOCs). At the same time, it is not inferior in terms of printing speed, effect, color and glossiness.

[0003] The patent application document with publication number CN101665639A discloses a water-based ink, which contains the following components in weight ratio: 30-35 parts of water-based polyurethane resin, 30-35 parts of water-based pigment, 3-5 parts of propylene glycol, 1-1.5 parts of dimethylethanolamine and 20-30 parts of water.

[0004] The water-based ink in the patent application document uses water-based polyurethane resin alone as a binder, and has slightly poor adhesion. Summary of the invention

[0005] In order to further improve the adhesion of water-based ink, the present application provides a water-based composite ink.

[0006] The present application provides a water-based composite ink, which adopts the following technical solution:

[0007] A water-based composite ink, comprising 50-70 parts by weight of a water-based resin, 15-25 parts by weight of a pigment, 12-18 parts by weight of a modified starch, 0.1-0.5 parts by weight of a defoamer, 30-60 parts by weight of a dispersion medium, and 3-5 parts by weight of triethanolamine;

[0008] The water-based resin includes modified water-based acrylic resin and water-based polyurethane;

[0009] The dispersion medium includes water, anhydrous ethanol and propylene glycol ethers;

[0010] The preparation method of the modified starch comprises the following steps:

[0011] (1) 12 to 18 parts by weight of starch, 0.6 to 0.9 parts by weight of sodium hexametaphosphate and water are uniformly mixed to obtain a starch emulsion;

[0012] (2) treating the starch emulsion with plasma for 4 to 6 minutes to obtain a pretreated starch emulsion;

[0013] (3) The pretreated starch emulsion and catalyst A are mixed uniformly, the temperature is raised to 40-50° C., 1.8-2 parts by weight of acetic anhydride is added, and the pH of the system is maintained at 8.0-8.5, the temperature is kept for 5-9 hours, the temperature is lowered, the pre-modified starch is washed, and the pre-modified starch is obtained;

[0014] (4) After the pre-modified starch is further dispersed, the pre-modified starch is coated with a propylene glycol methyl ether acetate solution, and dried to obtain a modified starch;

[0015] The propylene glycol methyl ether acetate accounts for 15% to 25% of the starch mass.

[0016] Preferably, the propylene glycol methyl ether acetate solution comprises propylene glycol methyl ether acetate and anhydrous ethanol.

[0017] Preferably, the catalyst A is p-toluenesulfonic acid.

[0018] Preferably, the amount of p-toluenesulfonic acid used is 1% to 2% of the mass of starch.

[0019] Preferably, the preparation process of the water-based composite ink comprises the following steps:

[0020] S1: at 40-50° C., 50-70 parts by weight of an aqueous resin, 30-60 parts by weight of a dispersion medium and a portion of triethanolamine are uniformly mixed and cooled to obtain a resin dispersion;

[0021] S2: 15-25 parts by weight of pigment and 0.1-0.5 parts by weight of defoamer are mixed evenly, added to the resin dispersion, mixed evenly, and then 12-18 parts by weight of modified starch and another part of triethanolamine are added, mixed evenly, allowed to stand, filtered, and packaged to obtain a water-based composite ink;

[0022] The total amount of the triethanolamine is 3 to 5 parts by mass; the pH of the aqueous composite ink is 8.0 to 9.0.

[0023] By adopting the above technical scheme, firstly, modified water-based acrylic resin and water-based polyurethane are compounded to provide a basic performance basis for the ink, giving the ink good film-forming properties, adhesion and certain mechanical properties during the drying and film-forming process.

[0024] Secondly, the dispersion medium can effectively disperse and dissolve the pigment and water-based resin, and with the assistance of the defoamer, the pigment can be better mixed with the resin dispersion in a bubble-free environment, thereby ensuring the uniformity of ink coloring. In addition, by optimizing the ratio of water, anhydrous ethanol and propylene glycol ether in the dispersion medium, the evaporation rate of the composite ink can be balanced, ensuring that the ink has enough time to level on the printed substrate to form a smooth and flat ink film, and can further enhance the chemical bonding or physical adsorption between the ink and the substrate, thereby improving the adhesion of the ink to various substrates.

[0025] Finally, on the one hand, in the preparation process of modified starch, after being treated with acetic anhydride, the hydrophilicity of starch molecules is reduced and the chemical structure is changed, which is conducive to the dispersion of starch in the water-based ink system. After further coating with propylene glycol methyl ether acetate, the starch particles are effectively isolated from excessive contact with water molecules, thereby further improving the dispersion state of starch particles. This good dispersion state helps to achieve the stability and uniformity of ink coloring. At the same time, it can also adjust the viscosity and rheological properties of the ink, so that the ink has better transferability during the printing process and can be evenly coated on the printing substrate, thereby improving the uniformity of pigment distribution and helping to achieve stable and uniform coloring.

[0026] On the other hand, the modified starch can have a strong interaction with the water-based resin and can also enhance the compatibility of starch with other components in the ink. This dual action mechanism enhances the overall cohesion of the ink, making the ink a highly coordinated organic whole that can better resist the stress caused by the deformation of the substrate and maintain a close connection between the ink and the substrate surface, thereby improving the adhesion of the ink.

[0027] Preferably, the total mass of the anhydrous ethanol and propylene glycol ethers accounts for 30% to 40% of the total mass of the dispersion medium, and the mass ratio of the anhydrous ethanol to the propylene glycol ethers is 5 to 7:3 to 5.

[0028] Preferably, the propylene glycol ether is any one of propylene glycol methyl ether and propylene glycol ethyl ether.

[0029] By adopting the above technical scheme, on the one hand, the amount of ethanol in the dispersion medium is reduced, which effectively reduces the impact of the pungent odor of water-based ink on the environment and operators, and alleviates the odor problem; and the evaporation rate of propylene glycol ethers is relatively slow, which can adjust the evaporation rate of ethanol, avoid the surface conjunctiva problem caused by too fast evaporation of ethanol, and allow the solvent inside the ink to evaporate normally, thereby ensuring a more uniform drying process and ultimately forming a dry ink layer of good quality.

[0030] On the other hand, it promotes the dispersion and dissolution of water-based resins and pigments in water-based composite ink systems. It can make pigment particles better dissolved and evenly dispersed in the system through mechanisms such as steric hindrance and charge stabilization, preventing pigment agglomeration and precipitation, which greatly improves the stability and uniformity of ink coloring. Ethanol can make the ink better penetrate into the surface pores of some substrates during the drying process, increasing the contact area between the ink and the substrate. Propylene glycol ethers can interact with the groups on the surface of the substrate through their functional groups. The two synergistically enhance the chemical bonding or physical adsorption between the ink and the substrate, and improve the adhesion of the ink to various substrates.

[0031] Preferably, the mass ratio of the modified starch to the water-based resin is about 1:3-5.

[0032] Preferably, the waterborne polyurethane accounts for 60% to 75% of the mass of the waterborne resin.

[0033] By adopting the above technical solution, firstly, when the proportion of waterborne polyurethane is high, due to its own good flexibility, the ink can better adapt to the deformation of various substrates, reduce the cracking or peeling of the ink layer due to the deformation of the substrate, and thus significantly enhance the adhesion of the ink to the substrate. In contrast, the proportion of modified waterborne acrylic resin is low, and its rigid components will not excessively affect the dominant role of the flexibility of waterborne polyurethane. At the same time, the presence of modified waterborne acrylic resin can also provide some hardness support for the ink to a certain extent, so that the ink has a certain degree of softness to adapt to the changes in the substrate after adhesion, and has enough hardness to resist slight friction and scratches from the outside.

[0034] Secondly, the interaction between a high proportion of waterborne polyurethane and a low proportion of modified waterborne acrylic resin will form a unique network structure, in which the waterborne polyurethane molecular chains are intertwined and the modified waterborne acrylic resin molecules can be interspersed. This network structure increases the contact points and interaction forces between the ink and the substrate, thereby improving the adhesion of the ink.

[0035] Finally, the high proportion of water-based polyurethane has significant advantages for pigment dispersion and ink film formation. The flexibility and good compatibility of its molecular chain can wrap the pigment particles, prevent pigment agglomeration, and form a continuous and uniform film, thereby ensuring the uniformity of ink coloring.

[0036] Preferably, the preparation method of the modified waterborne acrylic resin comprises the following steps:

[0037] S11: Evenly mix the epoxy resin and a part of the polymerization inhibitor, raise the temperature to 65-75°C, add acrylic acid, catalyst B and another part of the polymerization inhibitor and mix evenly, then raise the temperature to 90-100°C, react for 1-1.5 hours, and when the acid value is not higher than 5 mgKOH / g, stop the reaction, cool down, and obtain epoxy acrylate;

[0038] S12: using a solvent thermal reaction method, first adding a portion of a mixture of monomer A, monomer B and an initiator, and then adding epoxy acrylate and another portion of a mixture of monomer A, monomer B and an initiator, heating to 80-90° C., keeping the temperature for 2-3 hours, cooling, adjusting the pH to 7-8, distilling, washing and drying to obtain a modified waterborne acrylic resin;

[0039] The molar ratio of the epoxy resin to the acrylic acid is 1:1-1.2; the ratio of the molar number of the epoxy acrylate to the total molar number of the monomer A and the monomer B is 1:1-2;

[0040] The monomer A is any one of hydroxyethyl acrylate and hydroxypropyl acrylate;

[0041] The monomer B is any one of methoxyethyl methacrylate and methoxyethyl acrylate;

[0042] The molar ratio of monomer A to monomer B is 2-3:1.

[0043] Preferably, the catalyst B is triethylamine.

[0044] Preferably, the polymerization inhibitor comprises hydroquinone and phenothiazine, wherein the hydroquinone accounts for 0.05% to 0.1% of the total mass of the epoxy resin and the acrylic acid, and the phenothiazine accounts for 10% to 30% of the mass of the hydroquinone.

[0045] Preferably, the triethylamine accounts for 0.5% to 0.9% of the mass of the epoxy resin.

[0046] Preferably, the initiator is azobisisobutyronitrile.

[0047] Preferably, the azobisisobutyronitrile accounts for 0.8% to 1% of the total mass of hydroxyethyl acrylate and methoxyethyl methacrylate.

[0048] By adopting the above technical solution, firstly, epoxy acrylate is pre-synthesized by using epoxy resin and acrylic acid, thereby laying a foundation for subsequently improving adhesion.

[0049] Secondly, by adding some monomers to react first, the monomer concentration in the initial stage of the reaction is relatively low, the polymerization rate will not be too fast, and the polymer molecular chains can grow and interact in an orderly manner, reducing the possibility of gelation. At the same time, the first formed part of the polymer can be used as a dispersion medium for subsequent reactions, helping the newly added epoxy acrylate and monomers to be better dispersed in the system. This can avoid excessive local monomer concentration or over-concentration of the reaction, thereby reducing the risk of gel formation. At the same time, this step-by-step reaction method is also conducive to the uniform dissipation of reaction heat, preventing gelation caused by local overheating.

[0050] Finally, monomer A can not only increase the stability of the resin in water, thereby increasing the water solubility of the modified waterborne acrylic resin, but also relatively reduce the amount of carboxyl-containing monomers, thereby improving the chemical stability of the resin and better maintaining its adhesion to the substrate under various environmental conditions.

[0051] The use of monomer B in compounding makes the compounded water-based acrylic resin have a certain hydrophobicity. When the ink comes into contact with water or is in a humid environment, this hydrophobicity can prevent the ink from swelling and softening due to water absorption, thereby maintaining close contact between the ink and the substrate.

[0052] At the same time, the steric hindrance between the molecular chains of the compounded water-based acrylic resin increases, and the arrangement of the molecular chains changes, so that the functional groups on the molecular chains (such as hydroxyl, methoxy, etc.) have more opportunities to be exposed to the outside. For the functional groups on the surface of the substrate, especially polypropylene and polyethylene substrates, the hydroxyl groups on the molecular chains of the water-based acrylic resin can be closely combined with them through hydrogen bonds and other interactions, while functional groups such as methoxy can produce certain van der Waals interactions with the surface of the substrate through their special electron cloud distribution. Although the van der Waals force is relatively weak, it can also enhance the bonding force between the ink and the substrate under the joint action of multiple methoxy functional groups. Moreover, the stretched molecular chains can better adapt to the uneven microstructure of the substrate surface, increase the contact area and contact points with the functional groups or microstructures on the surface of the substrate, thereby further enhancing the interaction between the ink and the substrate and effectively improving the adhesion of the ink.

[0053] The change in the molecular chain structure of the compounded resin is also beneficial to the dispersion of the pigment. Due to the increase in the steric hindrance of the molecular chain, the resin can better wrap the pigment particles, prevent the pigment from agglomerating, and can be more evenly distributed in the resin body, thereby improving the coloring uniformity of the ink.

[0054] Preferably, the water-based composite ink further comprises nylon powder accounting for 0.5% to 2% of the total mass of the ink.

[0055] Preferably, the nylon powder is pretreated nylon powder, and the preparation method of the pretreated nylon powder comprises the following steps:

[0056] At 60-70° C., nylon powder and 10%-13% of propylene glycol random polyether GPE-3000 by weight of the nylon powder are uniformly mixed, and the temperature is lowered to obtain pretreated nylon powder.

[0057] Preferably, a portion of pretreated nylon powder is first added in step S1, and then in step S2, another portion of pretreated nylon powder is added after the modified starch.

[0058] By adopting the above technical solution, the pre-treated nylon powder is added in the early stage, which helps to improve the compatibility of the modified water-based acrylic resin and water-based polyurethane to a certain extent, and can also adjust the viscosity and fluidity of the ink. During the mixing process, it can optimize the rheological properties of the system, making the modified water-based acrylic resin and water-based polyurethane easier to disperse with each other. From a microscopic perspective, nylon powder particles can fill the gaps between the two resin molecules, effectively alleviating the phase separation problem caused by different intermolecular forces, thereby significantly improving the compatibility of the two.

[0059] The nylon powder added after the modified starch can produce a synergistic effect with the modified starch. The modified starch can provide certain adhesion and flexibility for the ink, and the addition of nylon powder can further enhance this adhesion performance. The particles of nylon powder can be filled in the structure formed by the modified starch to make the ink system more dense. When the ink is attached to the substrate, this dense structure can better resist the external shear force and tension. This part of nylon powder can also cooperate with the nylon powder added in step S1, and they can form a continuous and stable reinforcement network inside the ink, strengthen the structure of the ink from the inside, enhance the cohesion of the ink film, make the ink film more dense and tough, thereby improving the adhesion of the ink.

[0060] In summary, the present application includes at least one of the following beneficial technical effects:

[0061] 1. The present application adopts a high proportion of waterborne polyurethane and a low proportion of modified waterborne acrylic resin to interact with each other, which will form a unique network structure. The waterborne polyurethane molecular chains are intertwined, and the modified waterborne acrylic resin molecules can be interspersed therein. This network structure increases the contact points and interaction between the ink and the substrate, thereby improving the adhesion of the ink and the uniformity of coloring. At the same time, the modified starch can also produce a strong interaction with the waterborne resin, and can also enhance the compatibility of starch with other components in the ink. This dual action mechanism enhances the overall cohesion of the ink, making the ink a highly coordinated organic whole, which can better resist the stress caused by the deformation of the substrate and maintain the close connection between the ink and the surface of the substrate, thereby improving the adhesion of the ink.

[0062] 2. The present application also adopts propylene glycol ethers and ethanol, water as a composite dispersion medium, which not only reduces the amount of ethanol in the dispersion medium, effectively reduces the impact of the pungent odor of water-based ink on the environment and operators, but also can improve the stability and uniformity of ink coloring, enhance the chemical bonding or physical adsorption between the ink and the substrate, and improve the adhesion of the ink to various substrates.

[0063] 3. This application also introduces nylon powder. The pretreated nylon powder promotes the compatibility of modified water-based acrylic resin and water-based polyurethane to a certain extent through various means, helps to form a more stable and compact overall structure of the ink, and works together to enhance the bonding force between the ink and the printing substrate. DETAILED DESCRIPTION

[0064] The present application is further described in detail below with reference to the embodiments.

[0065] In the following examples and preparations:

[0066] The starch is corn starch, in which the proportion of amylose molecules is about 55%-60%.

[0067] Nylon powder was purchased from Shenzhen Hansen Plastic Technology Co., Ltd. Nylon powder is a mixture of 70% 200 mesh particles and 30% 500 mesh particles;

[0068] Carbon black was purchased from Shandong Kasong New Materials Co., Ltd. The carbon black consisted of 40% 20-40 nm particles and 60% 60-100 nm particles;

[0069] The defoamer was glycerol random polyether GPE-3000, with an acid value of no more than 0.5 mgKOH / g and a pH value (1% aqueous solution) of 6, purchased from Nantong Chenrun Chemical Co., Ltd.

[0070] Waterborne polyurethane was purchased from Anhui Dawei Huatai New Material Technology Co., Ltd.

[0071] Preparation Examples 1-3 Modified Starch

[0072] Preparation Example 1

[0073] (1) Add 107.4 g of deionized water into a container equipped with a stirring device, then add 0.6 g of sodium hexametaphosphate, stir at a stirring speed of 150 rpm until it is completely dissolved, continue stirring for 10 min, adjust the stirring speed to 300 rpm, then slowly add 12 g of corn starch, stir for 40 min, and obtain a starch emulsion;

[0074] (2) The starch emulsion was treated by a mixed gas atmospheric pressure plasma jet device with a power of 120 W and a distance of about 2 to 3 cm. During the treatment, the stirring speed was 80 rpm and the treatment time was 4 min to obtain a pretreated starch emulsion;

[0075] (3) Add 0.12g of p-toluenesulfonic acid to the pretreated starch emulsion, stir for 10min at a stirring speed of 150rmp, heat in a water bath to 40°C, slowly drop 1.8g of acetic anhydride and 5% by mass sodium hydroxide, stir while dropping, and maintain the system pH at 8.0-8.5. After the addition is completed, continue stirring and keep warm at 40°C for 9h, cool to room temperature, adjust the stirring speed to 100rmp, slowly drop 5% by mass dilute hydrochloric acid until the pH is about 5, wash with deionized water twice the volume of the reaction system each time and filter until neutral, then wash with anhydrous ethanol 1 times the volume of the reaction system and filter twice, then place in a vacuum drying oven at 60°C, dry for 24h, cool to room temperature, and gently grind and disperse until it completely passes through a 400-mesh sieve to obtain pre-modified starch;

[0076] (4) 10 ml of anhydrous ethanol and 1.8 g of propylene glycol methyl ether acetate were stirred for 10 min at a stirring speed of 100 rpm to obtain a propylene glycol methyl ether acetate solution. The pre-modified starch was first transferred into a container with a stirrer and stirred at a stirring speed of 80 rpm for 5 min. The propylene glycol methyl ether acetate solution was then slowly sprayed. After the spraying was completed, the stirring speed was adjusted to 150 rpm and the stirring was continued for 40 min. The mixture was then transferred into a vacuum drying oven at 60°C and dried for 4 h. The mixture was cooled to room temperature and ground and dispersed. The mixture was sieved through a 325-mesh screen to obtain modified starch.

[0077] The mixed gas is 95% argon and 5% oxygen.

[0078] Preparation Example 2

[0079] (1) Add 143.2 g of deionized water into a container equipped with a stirring device, then add 0.8 g of sodium hexametaphosphate, stir at a stirring speed of 150 rpm until it is completely dissolved, continue stirring for 10 min, adjust the stirring speed to 300 rpm, then slowly add 16 g of corn starch, stir for 40 min, and obtain a starch emulsion;

[0080] (2) The starch emulsion was treated by a mixed gas atmospheric pressure plasma jet device with a power of 120 W and a distance of about 2 to 3 cm. During the treatment, the stirring speed was 80 rpm and the treatment time was 5 min to obtain a pretreated starch emulsion;

[0081] (3) Add 0.32g of p-toluenesulfonic acid to the pretreated starch emulsion, stir for 10min at a stirring speed of 150rmp, heat in a water bath to 50°C, slowly drop 1.9g of acetic anhydride and 5% by mass sodium hydroxide, stir while dropping, maintain the system pH at 8.0-8.5, continue stirring and keep at 50°C for 5h, cool to room temperature, adjust the stirring speed to 100rmp, slowly drop 5% by mass dilute hydrochloric acid until the pH is about 5, wash with deionized water twice the volume of the reaction system each time and filter until neutral, then wash with anhydrous ethanol 1 times the volume of the reaction system and filter twice, then place in a vacuum drying oven at 60°C, dry for 24h, cool to room temperature, and grind and disperse slightly until it completely passes through a 400-mesh sieve to obtain pre-modified starch;

[0082] (4) 15 ml of anhydrous ethanol and 3.2 g of propylene glycol methyl ether acetate were stirred for 10 min at a stirring speed of 100 rpm to obtain a propylene glycol methyl ether acetate solution. The pre-modified starch was first transferred into a container with a stirrer and stirred at a stirring speed of 80 rpm for 5 min. The propylene glycol methyl ether acetate solution was then slowly sprayed. After the spraying was completed, the stirring speed was adjusted to 150 rpm and the stirring was continued for 40 min. The mixture was then transferred into a vacuum drying oven at 60°C and dried for 6 h. The mixture was cooled to room temperature and ground and dispersed. The mixture was sieved through a 325-mesh screen to obtain modified starch.

[0083] The mixed gas is 95% argon and 5% oxygen.

[0084] Preparation Example 3

[0085] (1) Add 161.1 g of deionized water into a container equipped with a stirring device, then add 0.9 g of sodium hexametaphosphate, stir at a stirring speed of 150 rpm until it is completely dissolved, continue stirring for 10 min, adjust the stirring speed to 300 rpm, then slowly add 18 g of corn starch, stir for 40 min, and obtain a starch emulsion;

[0086] (2) The starch emulsion was treated by a mixed gas atmospheric pressure plasma jet device with a power of 120 W and a distance of about 2 to 3 cm. During the treatment, the stirring speed was 80 rpm and the treatment time was 6 min to obtain a pretreated starch emulsion;

[0087] (3) Add 0.27g of p-toluenesulfonic acid to the pretreated starch emulsion, stir for 10min at a stirring speed of 150rmp, heat in a water bath to 45°C, slowly drop 2g of acetic anhydride and 5% by mass sodium hydroxide, stir while dropping, maintain the system pH at 8.0-8.5, continue stirring and keep at 45°C for 7h after the addition is complete, cool to room temperature, adjust the stirring speed to 100rmp, slowly drop 5% by mass dilute hydrochloric acid until the pH is about 5, wash with deionized water twice the volume of the reaction system each time and filter until neutral, then wash with anhydrous ethanol once the volume of the reaction system and filter twice, then place in a vacuum drying oven at 60°C, dry for 24h, cool to room temperature, grind and disperse slightly until it completely passes through a 400-mesh sieve, and obtain pre-modified starch;

[0088] (4) 20 ml of anhydrous ethanol and 4.5 g of propylene glycol methyl ether acetate were stirred for 10 min at a stirring speed of 100 rpm to obtain a propylene glycol methyl ether acetate solution. The pre-modified starch was first transferred to a container with a stirrer and stirred at a stirring speed of 80 rpm for 5 min. The propylene glycol methyl ether acetate solution was then slowly sprayed. After the spraying was completed, the stirring speed was adjusted to 150 rpm and the stirring was continued for 40 min. The mixture was then transferred to a vacuum drying oven at 60°C and dried for 8 h. The mixture was cooled to room temperature and ground and dispersed. The mixture was sieved through a 325-mesh screen to obtain modified starch.

[0089] The mixed gas is 95% argon and 5% oxygen.

[0090] Preparation Examples 4-6 Modified Waterborne Acrylic Resins

[0091] Preparation Example 4

[0092] S11: Add 1 mol of epoxy resin E-51, two-thirds of hydroquinone and two-thirds of phenothiazine into a three-necked flask, slowly stir and mix evenly and heat to 65°C, then slowly drop 1 mol of acrylic acid, triethylamine and the remaining mixture of hydroquinone and phenothiazine, heat and stir, heat to 90°C, react for 1.5 hours, take samples every 20 minutes to test the acid value of the reaction system, stop the reaction after the acid value drops to 5 mgKOH / g, cool down, and obtain epoxy acrylate;

[0093] The amount of hydroquinone used accounts for 0.05% of the total mass of epoxy resin E-51 and acrylic acid, the amount of phenothiazine used accounts for 10% of the mass of hydroquinone, and the amount of triethylamine used accounts for 0.5% of the mass of epoxy resin E-51;

[0094] S12: In another three-necked flask equipped with a thermometer, a condenser and a receiving bottle, add 260 ml of ethanol and stir and heat to its reflux temperature of about 78°C. After the reflux is stable, add about one-third of the uniform mixture of hydroxyethyl acrylate, methoxyethyl methacrylate and azobisisobutyronitrile within 20 minutes. After 15 minutes of the addition, start to add the dissolved 0.8 mol of epoxy acrylate and the remaining uniform mixture of hydroxyethyl acrylate, methoxyethyl methacrylate and azobisisobutyronitrile. Add for about 3 hours. After the addition is completed, , heat to 80 ℃, keep warm for 3h, add a small amount of azobisisobutyronitrile in the middle, then cool to 50 ℃, stir and add ammonia water to neutralize the system to pH 7, then keep warm and stir for 30min, slowly heat to 35 ℃ at 40mmHg, distill. When no liquid drips in the receiving bottle and the thermometer reading is stable, the distillation is completed. First use 2 times the amount of deionized water to wash, then use 2 times the amount of petroleum ether to wash, then transfer to a vacuum drying oven, dry at 70 ℃ for 12h, cool naturally, and obtain a modified water-based acrylic resin.

[0095] Among them, the amount of hydroxyethyl acrylate is 0.6 mol, the amount of methoxyethyl methacrylate is 0.2 mol, azobisisobutyronitrile accounts for 0.8% of the total mass of hydroxyethyl acrylate and methoxyethyl methacrylate, and the amount of azobisisobutyronitrile added in the middle is about 10% of the total amount of azobisisobutyronitrile used in the early stage.

[0096] Preparation Example 5

[0097] S11: 1 mol of epoxy resin E-51, two-thirds of hydroquinone and two-thirds of phenothiazine are added to a three-necked flask in sequence, slowly stirred to mix evenly and heated to 70°C, then 1.1 mol of acrylic acid, triethylamine and the remaining hydroquinone and phenothiazine are slowly added dropwise at the same time, heated and stirred, and heated to 95°C. After reacting for 1 hour, samples are taken every 20 minutes to test the acid value of the reaction system. When the acid value drops to 5 mgKOH / g, the reaction is stopped, and the temperature is lowered to obtain epoxy acrylate;

[0098] The amount of hydroquinone used accounts for 0.08% of the total mass of epoxy resin E-51 and acrylic acid, the amount of phenothiazine used accounts for 20% of the mass of hydroquinone, and the amount of triethylamine used accounts for 0.7% of the mass of epoxy resin E-51;

[0099] S12: In another three-necked flask equipped with a thermometer, a condenser and a receiving bottle, add 260 ml of ethanol and stir and heat to its reflux temperature of about 78°C. After the reflux is stable, add about one-third of the uniform mixture of hydroxyethyl acrylate, methoxyethyl methacrylate and azobisisobutyronitrile dropwise within 20 minutes. After 15 minutes of dropwise addition, start to dropwise add 0.6 mol of dissolved epoxy acrylate and the remaining mixture of hydroxyethyl acrylate, methoxyethyl methacrylate and azobisisobutyronitrile. Add dropwise for about 3 hours. After the addition is completed, raise Heat to 85°C, keep warm for 2h, add a small amount of azobisisobutyronitrile in the middle, then cool to 50°C, stir and add ammonia water dropwise to neutralize the system to pH 7.5, then keep warm and stir for 30min, slowly heat to 35°C at 40mmHg, distill. When no liquid drips from the receiving bottle and the thermometer reading is stable, the distillation is completed. First wash with 2 times the amount of deionized water, then wash with 2 times the amount of petroleum ether, then transfer to a vacuum drying oven, dry at 70°C for 12h, cool naturally, and obtain a modified water-based acrylic resin.

[0100] Among them, the amount of hydroxyethyl acrylate is 0.8 mol, the amount of methoxyethyl methacrylate is 0.4 mol, azobisisobutyronitrile accounts for 0.9% of the total mass of hydroxyethyl acrylate and methoxyethyl methacrylate, and the amount of azobisisobutyronitrile added in the middle is about 10% of the total amount of azobisisobutyronitrile used in the early stage.

[0101] Preparation Example 6

[0102] S11: Add 1 mol of epoxy resin E-51, two-thirds of hydroquinone and two-thirds of phenothiazine into a three-necked flask, slowly stir and mix evenly and heat to 75°C, then slowly drop 1.2 mol of acrylic acid, triethylamine and the remaining hydroquinone and phenothiazine at the same time, heat and stir, raise the temperature to 100°C, react for 1 hour, take samples every 20 minutes to test the acid value of the reaction system, stop the reaction when the acid value drops to 5 mgKOH / g, cool down, and obtain epoxy acrylate;

[0103] The amount of hydroquinone used accounts for 0.1% of the total mass of the epoxy resin and acrylic acid, the amount of phenothiazine used accounts for 30% of the mass of hydroquinone, and the amount of triethylamine used accounts for 0.9% of the mass of the epoxy resin;

[0104] S12: In another three-necked flask equipped with a thermometer, a condenser and a receiving bottle, add 260 ml of ethanol and stir and heat to its reflux temperature of about 78°C. After the reflux is stable, add about one-third of the uniform mixture of hydroxypropyl acrylate, methoxyethyl acrylate and azobisisobutyronitrile within 20 minutes. After 15 minutes of the addition, start to add 1 mol of dissolved epoxy acrylate and the remaining uniform mixture of hydroxypropyl acrylate, methoxyethyl acrylate and azobisisobutyronitrile. Add for about 3 hours. After the addition is completed, heat up. To 90 ℃, keep warm for 2h, add a small amount of azobisisobutyronitrile in the middle, then cool to 50 ℃, stir and add ammonia water to neutralize the system to pH 8, then keep warm and stir for 30min, slowly heat to 35 ℃ at 40mmHg, distill. When no liquid drips in the receiving bottle and the thermometer reading is stable, the distillation is completed. First use 2 times the amount of deionized water to wash, then use 2 times the amount of petroleum ether to wash, then transfer to a vacuum drying oven, dry at 70 ℃ for 12h, cool naturally, and obtain a modified water-based acrylic resin.

[0105] Among them, the amount of hydroxypropyl acrylate is 1 mol, the amount of methoxyethyl acrylate is 0.5 mol, azobisisobutyronitrile accounts for 1% of the total mass of hydroxypropyl acrylate and methoxyethyl acrylate, and the amount of azobisisobutyronitrile added in the middle is about 10% of the total amount of azobisisobutyronitrile used in the early stage.

[0106] Comparative Preparation Example 1 Modified Starch

[0107] (1) Add 107.4 g of deionized water into a container equipped with a stirring device, then add 0.6 g of sodium hexametaphosphate, stir at a stirring speed of 150 rpm until it is completely dissolved, continue stirring for 10 min, adjust the stirring speed to 300 rpm, then slowly add 12 g of corn starch, stir for 40 min, and obtain a starch emulsion;

[0108] (2) The starch emulsion was treated with a high-purity argon atmospheric pressure plasma jet device with a power of 120 W and a distance of about 2 to 3 cm. During the treatment, the stirring speed was 80 rpm and the treatment time was 4 min. The starch emulsion was then placed in a vacuum drying oven at 60 ° C. After drying for 24 h, it was cooled to room temperature and slightly ground and dispersed until it completely passed through a 325-mesh sieve to obtain a pre-modified starch.

[0109] Comparative Preparation Example 2 Modified Starch

[0110] (1) Add 107.4 g of deionized water into a container equipped with a stirring device, then add 0.6 g of sodium hexametaphosphate, stir at a stirring speed of 150 rpm until it is completely dissolved, continue stirring for 10 min, adjust the stirring speed to 300 rpm, then slowly add 12 g of corn starch, stir for 40 min, and obtain a starch emulsion;

[0111] (2) The starch emulsion was treated with a high-purity argon atmospheric pressure plasma jet device at a power of 120 W and a distance of about 2 to 3 cm. During the treatment, the stirring speed was 80 rpm and the treatment time was 4 min to obtain a pretreated starch emulsion;

[0112] (3) Add 0.12 g of p-toluenesulfonic acid to the pretreated starch emulsion, stir for 10 min at a stirring speed of 150 rmp, heat in a water bath to 40°C, slowly drop 1.8 g of acetic anhydride and 5% by mass sodium hydroxide, stir while dropping, and maintain the system pH at 8.0-8.5. After the addition is completed, continue stirring and keep warm at 40°C for 9 h, cool to room temperature, adjust the stirring speed to 100 rmp, slowly drop 5% by mass dilute hydrochloric acid until the pH is about 5, wash with deionized water twice the volume of the reaction system each time and filter until neutral, then wash with anhydrous ethanol 1 times the volume of the reaction system and filter twice, then place in a vacuum drying oven at 60°C, dry for 24 h, cool to room temperature, and gently grind and disperse until it completely passes through a 325-mesh sieve to obtain pre-modified starch.

[0113] Comparative Preparation Example 3 Modified Waterborne Acrylic Resin

[0114] The difference between this comparative preparation example and preparation example 4 is that the same molar number of ethyl methacrylate is used to replace methoxyethyl methacrylate.

[0115] The rest is the same as Preparation Example 4.

[0116] Comparative Preparation Example 4 Modified Waterborne Acrylic Resin

[0117] In another three-necked flask with a thermometer, a condenser and a receiving bottle, add 260 ml of ethanol and stir and heat to its reflux temperature of about 78°C. After the reflux is stable, add a uniform mixture of acrylic acid, hydroxyethyl acrylate, methoxyethyl methacrylate and azobisisobutyronitrile and add dropwise for about 3 hours. After the addition is complete, heat to 80°C and keep warm for 3 hours. In the middle, add a small amount of azobisisobutyronitrile, then cool to 50°C, stir and add ammonia water dropwise to neutralize the system to pH 7, then keep warm and stir for 30 minutes, slowly heat to 35°C at 40 mmHg, and distill. When no liquid drops from the receiving bottle and the thermometer reading is stable, the distillation is completed. First, use 2 times the amount of deionized water to wash, then use 2 times the amount of petroleum ether to wash, then transfer to a vacuum drying oven, dry at 70°C for 12 hours, and cool naturally to obtain a modified water-based acrylic resin.

[0118] Among them, the amount of acrylic acid used is 1 mol, the amount of hydroxyethyl acrylate used is 0.6 mol, the amount of methoxyethyl methacrylate used is 0.2 mol, azobisisobutyronitrile accounts for 0.8% of the total mass of acrylic acid, hydroxyethyl acrylate and methoxyethyl methacrylate, and the amount of azobisisobutyronitrile added in the middle is about 10% of the total amount of azobisisobutyronitrile used in the early stage.

[0119] An embodiment of a water-based composite ink of the present application is as follows:

[0120] Example 1

[0121] The present embodiment provides a water-based composite ink, which includes 20g of modified water-based acrylic resin, 30g of water-based polyurethane, 15g of carbon black, 12g of modified starch, 0.1g of defoaming agent, 18g of deionized water, 7.5g of anhydrous ethanol, 4.5g of propylene glycol methyl ether and 3g of triethanolamine.

[0122] This embodiment also provides a process for preparing a water-based composite ink, comprising the following steps:

[0123] S1: At 40°C, 18g of deionized water, 7.5g of anhydrous ethanol, and 4.5g of propylene glycol methyl ether were placed in a vacuum homogenizer and stirred for 20min at a stirring speed of 150rmp. Then, the stirring speed was adjusted to 200rmp, and 20g of modified water-based acrylic resin and 30g of water-based polyurethane were slowly added without stopping stirring. After the addition was completed, 1.5g of triethanolamine was added, and the mixture was stirred for 20min. The mixture was naturally cooled to room temperature to obtain a resin dispersion, and the vacuum degree was maintained at -0.06MPa~-0.08MPa;

[0124] S2: 15g of carbon black and 0.1g of defoamer were pre-stirred and mixed for 10min at a stirring speed of 60rmp, and then the uniformly mixed carbon black and defoamer and the resin dispersion prepared in step S1 were simultaneously transferred to the dispersion kettle, stirred and mixed at 1800rmp for 45min, and then the stirring speed was adjusted to 800rmp, and the stirring was continued for 15min. If bubbles were generated during this period, 0.01g of defoamer could be added in portions, and the total amount should not exceed 0.1g. After adding the defoamer, the stirring was continued for not less than 10min, and then 12g of modified starch and 1.5g of triethanolamine were slowly added. Amine, stirring speed is still 800rmp, stirring and mixing for 40min, during which the system pH is tested every 10-15min to maintain the system pH between 8.0 and 9.0. If the pH value deviates, the amount of triethanolamine added can be adjusted appropriately, and the amount adjusted each time should not exceed 0.5g. At the same time, after fully stirring, the pH value is tested again. After stirring and mixing, the ink in the dispersion kettle is transferred to a clean, sealed static container. After standing for 3h in an environment with a temperature of 25±2℃ and a relative humidity of 40%-60%, it is filtered and packaged to obtain a water-based composite ink.

[0125] Among them, the modified starch comes from Preparation Example 1, and the modified acrylic resin comes from Preparation Example 4.

[0126] Before use, carbon black was placed in a vacuum drying oven at 100°C for 2 h.

[0127] Example 2

[0128] The present embodiment provides a water-based composite ink, which includes 20g of modified water-based acrylic resin, 50g of water-based polyurethane, 25g of carbon black, 18g of modified starch, 0.5g of defoaming agent, 40.8g of deionized water, 11.2g of anhydrous ethanol, 8g of propylene glycol ethyl ether and 5g of triethanolamine.

[0129] This embodiment also provides a process for preparing a water-based composite ink, comprising the following steps:

[0130] S1: At 50°C, 40.8g of deionized water, 11.2g of anhydrous ethanol, and 8g of propylene glycol ethyl ether were placed in a vacuum homogenizer and stirred for 20min at a stirring speed of 150rmp. Then, the stirring speed was adjusted to 200rmp, and 20g of modified water-based acrylic resin and 50g of water-based polyurethane were slowly added without stopping stirring. After the addition was completed, 3g of triethanolamine was added, and the mixture was stirred for 20min. Then, the mixture was naturally cooled to room temperature to obtain a resin dispersion. The vacuum degree was maintained at -0.06MPa~-0.08MPa.

[0131] S2: 25g of carbon black and 0.5g of defoamer were pre-stirred and mixed for 10min at a stirring speed of 60rmp, and then the uniformly mixed carbon black and defoamer and the resin dispersion prepared in step S1 were simultaneously transferred into a dispersion kettle, stirred and mixed at 1800rmp for 45min, and then the stirring speed was adjusted to 800rmp, and the stirring was continued for 15min. If bubbles were generated during this period, 0.02g of defoamer could be added in portions, and the total amount should not exceed 0.2g. After adding the defoamer, the stirring was continued for not less than 10min, and then 18g of modified starch and 2g of triethanolamine were slowly added. , the stirring speed remains at 800rmp, stirring and mixing for 40min, during which the system pH is detected every 10~15min to maintain the system pH between 8.0~9.0. If the pH value deviates, the amount of triethanolamine added can be adjusted appropriately, and the amount adjusted each time should not exceed 0.5g. At the same time, after fully stirring, the pH value is detected again. After stirring and mixing, the ink in the dispersion kettle is transferred to a clean, sealed static container. After standing for 3h in an environment with a temperature of 25±2℃ and a relative humidity of 40%~60%, it is filtered and packaged to obtain a water-based composite ink.

[0132] Among them, the modified starch comes from Preparation Example 2, and the modified acrylic resin comes from Preparation Example 5.

[0133] Before use, carbon black was placed in a vacuum drying oven at 100°C for 2 h.

[0134] Example 3

[0135] The present embodiment provides a water-based composite ink, which includes 15g of modified water-based acrylic resin, 45g of water-based polyurethane, 20g of carbon black, 16g of modified starch, 0.4g of defoaming agent, 30g of deionized water, 9g of anhydrous ethanol, 4g of propylene glycol ethyl ether and 4g of triethanolamine.

[0136] This embodiment also provides a process for preparing a water-based composite ink, comprising the following steps:

[0137] S1: At 45°C, 30g of deionized water, 9g of anhydrous ethanol, and 4g of propylene glycol ethyl ether were placed in a vacuum homogenizer and stirred for 20min at a stirring speed of 150rmp. Then, the stirring speed was adjusted to 200rmp, and 15g of modified water-based acrylic resin and 45g of water-based polyurethane were slowly added without stopping stirring. After the addition was completed, 2g of triethanolamine was added, and the mixture was stirred for 20min. Then, the mixture was naturally cooled to room temperature to obtain a resin dispersion. The vacuum degree was maintained at -0.06MPa~-0.08MPa.

[0138] S2: 20g of carbon black and 0.4g of defoamer were pre-stirred and mixed for 10min at a stirring speed of 60rmp, and then the uniformly mixed carbon black and defoamer and the resin dispersion prepared in step S1 were simultaneously transferred into a dispersion kettle, stirred and mixed at 1800rmp for 45min, and then the stirring speed was adjusted to 800rmp, and stirring was continued for 15min. If bubbles were generated during this period, 0.02g of defoamer could be added in portions, and the total amount should not exceed 0.2g. After adding the defoamer, stirring was continued for not less than 10min, and then 16g of modified starch and 2g of triethanolamine were slowly added. , the stirring speed remains at 800rmp, stirring and mixing for 40min, during which the system pH is detected every 10~15min to maintain the system pH between 8.0~9.0. If the pH value deviates, the amount of triethanolamine added can be adjusted appropriately, and the amount adjusted each time should not exceed 0.5g. At the same time, after fully stirring, the pH value is detected again. After stirring and mixing, the ink in the dispersion kettle is transferred to a clean, sealed static container. After standing for 3h in an environment with a temperature of 25±2℃ and a relative humidity of 40%~60%, it is filtered and packaged to obtain a water-based composite ink.

[0139] Among them, the modified starch comes from Preparation Example 3, and the modified acrylic resin comes from Preparation Example 6.

[0140] Before use, carbon black was placed in a vacuum drying oven at 100°C for 2 h.

[0141] Example 4

[0142] The difference between this embodiment and embodiment 3 is that:

[0143] Among them, the modified starch comes from Preparation Example 2, and the modified acrylic resin comes from Preparation Example 6.

[0144] The rest is the same as in Example 3.

[0145] Example 5

[0146] The present embodiment provides a water-based composite ink, which includes 15g of modified water-based acrylic resin, 45g of water-based polyurethane, 20g of carbon black, 16g of modified starch, 0.4g of defoaming agent, 30g of deionized water, 9g of anhydrous ethanol, 4g of propylene glycol ethyl ether, 4g of triethanolamine and 0.8g of nylon powder.

[0147] This embodiment also provides a process for preparing a water-based composite ink, comprising the following steps:

[0148] S1: At 45°C, first place 30g of deionized water, 9g of anhydrous ethanol, and 4g of propylene glycol ethyl ether in a vacuum homogenizer and stir and mix for 20min at a stirring speed of 150rmp, then adjust the stirring speed to 300rmp, slowly add 0.2g of nylon powder, stir and mix for 20min, then adjust the stirring speed to 200rmp, slowly add 15g of modified water-based acrylic resin and 45g of water-based polyurethane, stirring continuously during the period, after the addition is completed, add 2g of triethanolamine, continue stirring for 20min, and naturally cool to room temperature to obtain a resin dispersion, and the vacuum degree is maintained at -0.06MPa~-0.08MPa;

[0149] S2: 20g of carbon black and 0.4g of defoamer are pre-stirred and mixed for 10min at a stirring speed of 60rmp, and then the uniformly mixed carbon black and defoamer and the resin dispersion prepared in step S1 are simultaneously transferred into a dispersion kettle, stirred and mixed at 1800rmp for 45min, and then the stirring speed is adjusted to 800rmp, and the stirring is continued for 15min. If bubbles are generated during this period, 0.02g of defoamer can be added in portions, and the total amount shall not exceed 0.2g. After adding the defoamer, continue to stir for not less than 10min, and then slowly add 16g of modified starch and 2g of triethanolamine, and the stirring speed is still 800rmp. After stirring and mixing for 40min, the stirring speed is adjusted to 500rmp, and then 0.6g of nylon powder is slowly added, and stirred and mixed for 30min.

[0150] During the period, the pH value of the system is checked every 10 to 15 minutes to maintain the pH value between 8.0 and 9.0. If the pH value deviates, the amount of triethanolamine added can be adjusted appropriately, and the amount adjusted each time should not exceed 0.5 g. At the same time, the pH value should be checked again after sufficient stirring. After stirring and mixing, the ink in the dispersion kettle is transferred to a clean, sealed static container. After standing for 3 hours in an environment with a temperature of 25±2℃ and a relative humidity of 40% to 60%, it is filtered and packaged to obtain a water-based composite ink.

[0151] Among them, the modified starch comes from Preparation Example 3, and the modified acrylic resin comes from Preparation Example 6.

[0152] Before use, carbon black was placed in a vacuum drying oven at 100°C for 2 h.

[0153] The nylon powder is pretreated nylon powder, and the preparation method of the pretreated nylon powder comprises the following steps:

[0154] Under nitrogen atmosphere, at 60°C, 0.8 g of nylon powder was placed in a stirring container, and then 0.08 g of propylene glycol random polyether GPE-3000 was added dropwise, and the mixture was stirred for 30 minutes at a stirring speed of 100 rpm. The mixture was naturally cooled to room temperature to obtain pretreated nylon powder.

[0155] Before pretreatment, the nylon powder was placed in a vacuum drying oven at 80°C for 2 hours.

[0156] Example 6

[0157] The present embodiment provides a water-based composite ink, which includes 15g of modified water-based acrylic resin, 45g of water-based polyurethane, 20g of carbon black, 16g of modified starch, 0.4g of defoaming agent, 30g of deionized water, 9g of anhydrous ethanol, 4g of propylene glycol ethyl ether, 4g of triethanolamine and 2.1g of nylon powder.

[0158] This embodiment also provides a process for preparing a water-based composite ink, comprising the following steps:

[0159] S1: At 45°C, first place 30g of deionized water, 9g of anhydrous ethanol, and 4g of propylene glycol ethyl ether in a vacuum homogenizer and stir and mix for 20min at a stirring speed of 150rmp, then adjust the stirring speed to 300rmp, slowly add 0.7g of nylon powder, stir and mix for 20min, then adjust the stirring speed to 200rmp, slowly add 15g of modified water-based acrylic resin and 45g of water-based polyurethane, stirring continuously during the period, after the addition is completed, add 2g of triethanolamine, continue stirring for 20min, and naturally cool to room temperature to obtain a resin dispersion, and the vacuum degree is maintained at -0.06MPa~-0.08MPa;

[0160] S2: 20g of carbon black and 0.4g of defoamer are pre-stirred and mixed for 10min at a stirring speed of 60rmp, and then the uniformly mixed carbon black and defoamer and the resin dispersion prepared in step S1 are simultaneously transferred into a dispersion kettle, and stirred and mixed at 1800rmp for 45min, and then the stirring speed is adjusted to 800rmp, and stirring is continued for 15min. If bubbles are generated during this period, 0.02g of defoamer can be added in portions, and the total amount shall not exceed 0.2g. After adding the defoamer, stirring is continued for not less than 10min, and then 16g of modified starch and 2g of triethanolamine are slowly added, and the stirring speed is still 800rmp. After stirring and mixing for 40min, the stirring speed is adjusted to 500rmp, and then 1.4g of nylon powder is slowly added, and stirring and mixing is continued for 30min.

[0161] During the period, the pH value of the system is checked every 10 to 15 minutes to maintain the pH value between 8.0 and 9.0. If the pH value deviates, the amount of triethanolamine added can be adjusted appropriately, and the amount adjusted each time should not exceed 0.5 g. At the same time, the pH value should be checked again after sufficient stirring. After stirring and mixing, the ink in the dispersion kettle is transferred to a clean, sealed static container. After standing for 3 hours in an environment with a temperature of 25±2℃ and a relative humidity of 40% to 60%, it is filtered and packaged to obtain a water-based composite ink.

[0162] Among them, the modified starch comes from Preparation Example 3, and the modified acrylic resin comes from Preparation Example 6.

[0163] Before use, carbon black was placed in a vacuum drying oven at 100°C for 2 h.

[0164] The nylon powder is pretreated nylon powder, and the preparation method of the pretreated nylon powder comprises the following steps:

[0165] Under nitrogen atmosphere, at 70°C, 2.1 g of nylon powder was placed in a stirring container, and then 0.25 g of propylene glycol random polyether GPE-3000 was added dropwise, stirred and mixed for 40 minutes at a stirring speed of 100 rpm, and naturally cooled to room temperature to obtain pretreated nylon powder.

[0166] Before pretreatment, the nylon powder was placed in a vacuum drying oven at 80°C for 2 hours.

[0167] Example 7

[0168] The present embodiment provides a water-based composite ink, which includes 15g of modified water-based acrylic resin, 45g of water-based polyurethane, 20g of carbon black, 16g of modified starch, 0.4g of defoaming agent, 30g of deionized water, 9g of anhydrous ethanol, 4g of propylene glycol ethyl ether, 4g of triethanolamine and 3g of nylon powder.

[0169] This embodiment also provides a process for preparing a water-based composite ink, comprising the following steps:

[0170] S1: At 45°C, first place 30g of deionized water, 9g of anhydrous ethanol, and 4g of propylene glycol ethyl ether in a vacuum homogenizer and stir and mix for 20min at a stirring speed of 150rmp, then adjust the stirring speed to 300rmp, slowly add 1g of nylon powder, stir and mix for 20min, then adjust the stirring speed to 200rmp, slowly add 15g of modified water-based acrylic resin and 45g of water-based polyurethane, stirring without stopping during the period, after the addition is completed, add 2g of triethanolamine, continue stirring for 20min, and naturally cool to room temperature to obtain a resin dispersion, and the vacuum degree is maintained at -0.06MPa~-0.08MPa;

[0171] S2: 20g of carbon black and 0.4g of defoamer are pre-stirred and mixed for 10min at a stirring speed of 60rmp, and then the uniformly mixed carbon black and defoamer and the resin dispersion prepared in step S1 are simultaneously transferred into a dispersion kettle, stirred and mixed at 1800rmp for 45min, and then the stirring speed is adjusted to 800rmp, and the stirring is continued for 15min. If bubbles are generated during this period, 0.02g of defoamer can be added in portions, and the total amount shall not exceed 0.2g. After adding the defoamer, stirring is continued for not less than 10min, and then 16g of modified starch and 2g of triethanolamine are slowly added, and the stirring speed is still 800rmp. After stirring and mixing for 40min, the stirring speed is adjusted to 500rmp, and then 2g of nylon powder is slowly added, and stirred and mixed for 30min.

[0172] During the period, the pH value of the system is checked every 10 to 15 minutes to maintain the pH value between 8.0 and 9.0. If the pH value deviates, the amount of triethanolamine added can be adjusted appropriately, and the amount adjusted each time should not exceed 0.5 g. At the same time, the pH value should be checked again after sufficient stirring. After stirring and mixing, the ink in the dispersion kettle is transferred to a clean, sealed static container. After standing for 3 hours in an environment with a temperature of 25±2℃ and a relative humidity of 40% to 60%, it is filtered and packaged to obtain a water-based composite ink.

[0173] Among them, the modified starch comes from Preparation Example 3, and the modified acrylic resin comes from Preparation Example 6.

[0174] Before use, carbon black was placed in a vacuum drying oven at 100°C for 2 h.

[0175] The nylon powder is pretreated nylon powder, and the preparation method of the pretreated nylon powder comprises the following steps:

[0176] Under nitrogen atmosphere, at 65° C., 3 g of nylon powder was placed in a stirring container, and then 0.4 g of propylene glycol random polyether GPE-3000 was added dropwise, and the mixture was stirred for 50 min at a stirring speed of 100 rpm. The mixture was naturally cooled to room temperature to obtain pretreated nylon powder.

[0177] Before pretreatment, the nylon powder was placed in a vacuum drying oven at 80°C for 2 hours.

[0178] Comparative Example 1

[0179] The difference between this comparative example and Example 1 is:

[0180] The propylene glycol methyl ether was replaced by anhydrous ethanol of the same mass.

[0181] The rest is the same as in Example 1.

[0182] Comparative Example 2

[0183] The difference between this comparative example and Example 1 is:

[0184] The modified starch comes from Comparative Preparation Example 1.

[0185] The rest is the same as in Example 1.

[0186] Comparative Example 3

[0187] The difference between this comparative example and Example 1 is:

[0188] The modified starch comes from Comparative Preparation Example 2.

[0189] The rest is the same as in Example 1.

[0190] Comparative Example 4

[0191] The difference between this comparative example and Example 1 is:

[0192] The modified starch comes from Comparative Preparation Example 2, and the modified acrylic resin comes from Comparative Preparation Example 3.

[0193] The rest is the same as in Example 1.

[0194] Comparative Example 5

[0195] The difference between this comparative example and Example 1 is:

[0196] The modified starch comes from Comparative Preparation Example 2, and the modified acrylic resin comes from Comparative Preparation Example 4.

[0197] The rest is the same as in Example 1.

[0198] Performance Testing

[0199] Substrate: BOPP Reference standard: (1) According to GB / T13217.7-2023 "Test method for ink adhesion", the adhesion of the water-based composite inks in Examples 1 to 7 and Comparative Examples 1 to 5 was tested respectively. The test results are shown in Table 1;

[0200] (2) According to GB / T13217.1-2020 "Test Method for Color and Tinting Strength of Ink", the consistency and uniformity of the coloring of the water-based composite inks in Examples 1 to 7 and Comparative Examples 1 to 5 were tested respectively. The test results are shown in Table 1;

[0201] (3) According to GB / T13217.4-2020 “Test method for viscosity of liquid ink”, the viscosity of the aqueous composite inks in Examples 1 to 7 and Comparative Examples 1 to 5 was tested respectively. The test results are shown in Table 1.

[0202] 3. Water resistance test: The samples (thickness of about 1.5 μm) printed with the water-based composite inks of Examples 1 to 7 and Comparative Examples 1 to 5 were boiled in boiling water for 30 minutes. The acceptance standard was that the ink layer had no bubbles and no ink falling off.

[0203] Table 1 Performance test of water-based composite ink in Examples 1 to 7 and Comparative Examples 1 to 5

[0204]

[0205] By comparing and analyzing Example 1 and Comparative Examples 1 to 5, it can be seen that replacing propylene glycol methyl ether in the dispersion medium with anhydrous ethanol will reduce the solubility of some components in the ink and affect the dispersibility of the pigment, resulting in reduced adhesion and tinting power of the composite ink.

[0206] The use of acetic anhydride treatment and further coating with propylene glycol methyl ether acetate effectively isolates the starch particles from excessive contact with water molecules, thereby further improving the dispersion state of the starch particles. This good dispersion state helps to achieve the stability and uniformity of ink coloring. When interacting with the substrate and other components of the ink, the combination will be more closely, enhancing the integrity of the ink while also improving the adhesion of the ink.

[0207] When methoxyethyl methacrylate was replaced by ethyl methacrylate in the same molar amount, the adhesion of the obtained water-based composite ink was improved to a certain extent. This may be because: methoxyethyl methacrylate may help maintain better compatibility between the modified water-based acrylic resin and the water-based polyurethane, while enhancing the interfacial interaction with the substrate, thereby improving the adhesion of the ink and the uniformity of coloring.

[0208] Comparative analysis of Examples 1 to 4 shows that by optimizing the ratio of water-based acrylic resin, water-based polyurethane and other components, the performance of the prepared water-based composite ink is also optimized to varying degrees.

[0209] Comparative analysis of Examples 4 to 7 shows that the pretreated nylon powder promotes the compatibility of the modified water-based acrylic resin and the water-based polyurethane to a certain extent in various ways, helps to form a more stable and compact overall structure of the ink, and works together to further enhance the adhesion of the ink.

Claims

1. A water-based composite ink, characterized by: The water-based composite ink comprises 50-70 parts by mass of a water-based resin, 15-25 parts by mass of a pigment, 12-18 parts by mass of a modified starch, 0.1-0.5 parts by mass of a defoaming agent, 30-60 parts by mass of a dispersion medium, and 3-5 parts by mass of triethanolamine; The water-based resin includes modified water-based acrylic resin and water-based polyurethane; The dispersion medium includes water, anhydrous ethanol and propylene glycol ethers; The preparation method of the modified starch comprises the following steps: (1) 12 to 18 parts by mass of starch, 0.6 to 0.9 parts by mass of sodium hexametaphosphate, and water are uniformly mixed to obtain a starch emulsion; (2) Plasma-treating the starch emulsion for 4 to 6 minutes to obtain a pretreated starch emulsion; (3) The pretreated starch emulsion and catalyst A were mixed evenly, heated to 40-50°C, and then 1.8-2 parts by mass of acetic anhydride were added, and the pH of the system was maintained at 8.0-8.

5. The mixture was kept warm for 5-9 hours, cooled, washed, and dried to obtain pre-modified starch; (4) After the pre-modified starch is further dispersed, the pre-modified starch is coated with a propylene glycol methyl ether acetate solution and dried to obtain a modified starch; The propylene glycol methyl ether acetate accounts for 15% to 25% of the starch mass; The water-based composite ink also includes pretreated nylon powder accounting for 0.5% to 2% of the total mass of the ink. The preparation method of the pretreated nylon powder includes the following steps: uniformly mixing the nylon powder with propylene glycol random polyether GPE-3000 accounting for 10% to 13% of the mass of the nylon powder at 60 to 70° C., and cooling to obtain the pretreated nylon powder.

2. The water-based composite ink according to claim 1, characterized in that: The preparation process of the water-based composite ink comprises the following steps: S1: at 40-50° C., uniformly mix 50-70 parts by mass of an aqueous resin, 30-60 parts by mass of a dispersion medium, and a portion of triethanolamine, and cool to obtain a resin dispersion; S2: After uniformly mixing 15-25 parts by mass of pigment and 0.1-0.5 parts by mass of defoamer, add the mixture to the resin dispersion and mix evenly, then add 12-18 parts by mass of modified starch and another portion of triethanolamine, mix evenly, let stand, separate the solid and liquid, and package to obtain a water-based composite ink; The total amount of the triethanolamine is 3 to 5 parts by mass; and the pH of the aqueous composite ink is 8.0 to 9.

0.

3. The water-based composite ink according to claim 2, characterized in that: The total mass of the anhydrous ethanol and propylene glycol ethers accounts for 30% to 40% of the total mass of the dispersion medium, and the mass ratio of the anhydrous ethanol to the propylene glycol ethers is 5 to 7:3 to 5.

4. The water-based composite ink according to claim 3, characterized in that: The propylene glycol ether is any one of propylene glycol methyl ether and propylene glycol ethyl ether.

5. The water-based composite ink according to claim 1, characterized in that: The waterborne polyurethane accounts for 60% to 75% of the mass of the waterborne resin.

6. The water-based composite ink according to claim 5, characterized in that: The preparation method of the modified water-based acrylic resin comprises the following steps: S11: Evenly mix the epoxy resin and a portion of the polymerization inhibitor, raise the temperature to 65-75°C, add acrylic acid, catalyst B, and another portion of the polymerization inhibitor, mix evenly, and then raise the temperature to 90-100°C. After reacting for 1-1.5 hours, if the acid value is not higher than 5 mgKOH / g, stop the reaction, cool, and obtain epoxy acrylate; S12: using a solvent thermal reaction method, first adding a portion of the mixture of monomer A, monomer B, and an initiator, and then adding epoxy acrylate and another portion of the mixture of monomer A, monomer B, and an initiator, heating to 80-90° C., keeping the temperature for 2-3 hours, cooling, adjusting the pH to 7-8, distilling, washing, and drying to obtain a modified waterborne acrylic resin; The molar ratio of the epoxy resin to the acrylic acid is 1:1-1.2; the ratio of the molar number of the epoxy acrylate to the total molar number of monomer A and monomer B is 1:1-2; The monomer A is any one of hydroxyethyl acrylate and hydroxypropyl acrylate; The monomer B is any one of methoxyethyl methacrylate and methoxyethyl acrylate; The molar ratio of monomer A to monomer B is 2-3:

1.

7. The water-based composite ink according to claim 6, characterized in that: The polymerization inhibitor comprises hydroquinone and phenothiazine, wherein the hydroquinone accounts for 0.05% to 0.1% of the total mass of the epoxy resin and the acrylic acid, and the phenothiazine accounts for 10% to 30% of the mass of the hydroquinone.

Citation Information

Patent Citations

  • Aqueous ink

    CN101665639A

  • Weak solvent ink-jet ink

    CN104449042A

  • Scratching-resistant aqueous ink and preparation method thereof

    CN110183905A

  • Method for preparing high-substitution-degree acetylated starch by coupling electric field with ultrasound waves

    CN111303305A

  • Polymer-based pigment-bearing ink

    WO2008145258A1